An effective transformer less 7 level inverter with optimized PID and buck boost controller for grid-connected PV systems - Rao, B. Mohan; Khan, Mohammad Haseeb; Mangu, B. (Institute of Advanced Engineering and Science, 2025)
This research paper presents an effective transformer-less seven-level inverter with an optimized proportional-integral-derivative (PID) controller and buck-boost controller for grid-connected photovoltaic (PV) systems. The proposed model aims to achieve optimum power quality (PQ) in a hybrid power system integrating battery and PV. This is accomplished by utilizing a unified power quality conditioner (UPQC-PQ) with active and reactive power is developed, utilizing a hybrid metaheuristic algorithm named the honey badger algorithm (HBA) along with the equilibrium optimization algorithm (EOA), referred to as the honey badger equilibrium optimization (HBEO) algorithm. The PID controller in the proposed model is optimized using the HBEO algorithm, resulting in a highly efficient hybrid renewable energy system. By incorporating a 7-level multilevel inverter model with minimal switch usage (only 5 switches instead of 12), the proposed model ensures minimal switching losses. The proposed model is implemented and verified through the MATLAB/Simulink platform.